Perioperative Complications and Critical Care Management of a Patient with Pituitary Tumor Undergoing Endoscopic Endonasal Transsphenoidal Surgery (EETH) - Dananjaya, Dananjaya; Harijono, Bambang; Kriswidyatomo, Prihatma (Journal of Neonatal Surgery, 2025)
Pituitary tumours often necessitate complex surgical interventions, such as Endoscopic Endonasal Transsphenoidal Surgery (EETH), which carry significant perioperative risks, including fluid and electrolyte imbalances. This case report presents the critical care management of a 44-year-old male, Mr. N, who underwent EETH for a suspected craniopharyngioma. Mr N presented with progressive neurological symptoms, including headaches, right temporal hemianopia, and difficulty walking. Imaging revealed a large suprasellar mass and non-communicating hydrocephalus, leading to the placement of a Ventriculoperitoneal (VP) shunt prior to surgery. During the EETH procedure, the patient experienced a massive intraoperative haemorrhage of 4500 mL, necessitating the activation of a Massive Transfusion Protocol (MTP) and aggressive resuscitation efforts. Postoperatively, Mr. N was admitted to the ICU for intensive monitoring. His recovery was complicated by severe anaemia, cerebral salt wasting (CSW), and multiple episodes of cardiac arrest. Fluid resuscitation, electrolyte correction, and antimicrobial prophylaxis were initiated to stabilize the patient and prevent infection. Despite these interventions, Mr N's condition continued to decline, leading to family discussions on resuscitation preferences. Mr N ultimately succumbed to the complications related to a massive haemorrhage and critical care challenges. This case underscores the complexities of managing patients post-EETH and highlights the importance of a multidisciplinary approach and vigilant monitoring. Successful perioperative management in pituitary surgery requires anticipating complications like CSW and implementing rapid response protocols. Maintaining fluid and electrolyte balance is essential to improving outcomes in neurosurgical interventions